Penelusuran Aktivitas Antibakteri dari Kulit Akar Tumbuhan Medang Seluang (Litsea spathulata) terhadap Bakteri Uji Escherichia coli dan Shigella dysentriae - Munawar Munawar; Elfita Elfita (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2007)
Screening for antibacterial activity from root bark of Litsea spathulata had been done. Antibacterial test on each fraction showed that hexane had the highest activity followed by ethyl acetate and methanol. Major compound from antibacterial active fraction had been isolated. Identification of this compound was carried out applying phytochemistry assay and spectroscopic methods, i.e. ultraviolet (UV), infrared (IR), and Gas Chromatography- Mass Spectroscopic (GC-MS). Minimum inhibiting concentration (MIC) value of the active fraction was 780 mg/mL to Escherichia coli and 860 mg/mL to Shigella dysentriae.